Regulation of transient receptor potential channels by traditional Chinese medicines and their active ingredients - Yan, Shidu; Huang, Yuchan; Xiao, Qian; Su, Zixia; Xia, Lei; Xie, Jinling; Zhang, Fan; Du, Zhengcai; Hou, Xiaotao; Deng, Jiagang; Hao, Erwei (Frontiers in Pharmacology, 2022)
In recent years, activation of thermal transient receptor potential (TRP) ion channels at a range of temperatures has received widespread attention as a target for traditional Chinese medicine (TCM) to regulate body temperature and relieve pain. Discovery of transient receptor potential vanilloid 1 (TRPV1) was awarded a Nobel Prize, reflecting the importance of these channels. Here, the regulatory effects of TCMs and their active ingredients on TRP ion channels are reviewed, and future directions for research on the cold, hot, warm, cool, and neutral natures of TCMs are considered. In herbs with cold, hot, warm, cool, and neutral natures, we found 29 TCMs with regulatory effects on TRP ion channels, including Cinnamomi Cortex, Capsici Fructus, Rhei Radix et Rhizoma, Macleayae cordatae Herba, Menthae Haplocalycis Herba, and Rhodiolae Crenulatae Radix et Rhizoma. Although some progress has been made in understanding the regulation of TRP ion channels by TCMs and their ingredients, the molecular mechanism by which TCMs have this effect remains to be further studied. We hope this review will provide a reference for further research on the cold, hot, warm, cool, and neutral natures of TCMs.